O sztuce krasomówczej w Ćwiczeniach krasomówsko-prawnych Jana Bielskiego - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The work at hand deals with the art of orations in Jan Bielski’s Ćwiczenia krasomówsko-prawne. The analysis focused on the author›s remarks concerning rhetoric, which are to be found in the foreword, and in selected “juridical cases”. Rhetoric is perceived as helpful field in getting honours. Moreover, it is useful in unmasking the falsehood and reconciling antagonists. On the other hand, rhetoric is also shown as the “craft” which can serve vile, godless cells and which, “uncontrollable”, causes the disaster. Bielski’s Ćwiczenia... made young people aware, that acquaintance of rhetoric has a real influence on the outside world.